Reservations to multilateral human rights treaties - Huang, Yingliang (University of Ottawa (Canada), 2006)
Reservations to multilateral human rights treaties have become an important issue since the case of the Genocide Convention in 1951. Although the compatibility principle upheld by the International Court of Justice (ICJ) was codified in the 1969 Vienna Convention on the Law of Treaties (Vienna Convention), the current reservations mechanism is problematic and detrimental to human rights treaty-making. I will argue that the logical relation between the two standards comprising the compatibility principle has been lost under the Vienna Convention and it should be reintroduced by a competent body. For this purpose, I will analyze the characteristics of human rights treaties, clarify the permissibility of making reservations, go through the origin and development of the compatibility principle, and identify the problem of the current reservations mechanism, namely that the determination of the compatibility of reservations is left to individual States. The solution I will propose is that the ICJ should be conferred the competence to objectively determine the compatibility of reservations. Key words. the compatibility principle; the objective determination of compatibility
Keywords: Political Science, International Law and Relations.